RUSSIAN LITERATURE AND THE BRITISH POLITICAL ELITE: WHAT THE 19TH CENTURY TELLS THE 21ST (A FEW OBSERVATIONS) - M. P. Kizima (Концепт: философия, религия, культура, 2017)
This paper is dedicated to the study of the influence of Russian classical literature on the shaping of the image of Russia abroad. The development of international relations depends to a great extent on the fundamental cultural dichotomy of "them and us". The image of the "other" is constructed in different ways; one of the most productive sources for it is the classical literature of the "other" country, for it broadens the knowledge of the "other" and helps to create a basis for mutual understanding in peoples' minds. The study is based on the principles of historical, cultural and textual analysis. As a relevant historical example the author takes the situation in the 19th century Britain, at the time of the war between Russia and Turkey, 1877 - 78. Anti-Russian feelings were running high in Britain then (the anti-Russian campaign of those years reminds the researcher of the present-day situation). Yet, what attracts the author's attention is the fact that some representatives of the British political elite, led by W.E. Gladstone (1809 - 1898), maintained a more balanced and objective attitude towards Russia. Gladstone, leader of the Opposition to the Conservative Government, criticized the anti-Russian campaign waged by the Conservatives. He accused them of hypocrisy and double standards, spoke for an objective analysis of the foreign policy of Russia. Moreover, he emphasized the moral value of Russian victories, wrote that Russia made the decisive contribution to the liberation of the peoples of the Balkan Peninsular. The author proves that one of the factors that influenced Gladstone's position in this political controversy was Russian classical literature. This conclusion is based on the analysis of Gladstone's reading, his diaries and his works "The Friends and Foes of Russia" (1879) and "Russia and England" (1880). The analysis shows that Russian classical literature made its contribution to the shaping of Gladstone's deeper and more enlightened view of Russia and Russian foreign policy. In conclusion, the author points out that this historical experience maintains its significance in the 21st century, for classical literature moves with the times, and Russian classical literature continues exercising its positive influence on the image of Russia abroad, building bridges between Russia and other nations.